The organization of genome duplication is a critical determinant of the landscape of genome maintenance - Gómez-Escoda, Blanca; Wu, Pei-Yun Jenny (Genome Research, 2018)
Genome duplication is essential for cell proliferation, and the mechanisms regulating its execution are highly conserved. These processes give rise to a spatiotemporal organization of replication initiation across the genome, referred to as the replication program. Despite the identification of such programs in diverse eukaryotic organisms, their biological importance for cellular physiology remains largely unexplored. We address this fundamental question in the context of genome maintenance, taking advantage of the inappropriate origin firing that occurs when fission yeast cells lacking the Rad3/ATR checkpoint kinase are subjected to replication stress. Using this model, we demonstrate that the replication program quantitatively dictates the extent of origin de-regulation and the clustered localization of these events. Furthermore, our results uncover an accumulation of abnormal levels of single-stranded DNA (ssDNA) and the Rad52 repair protein at de-regulated origins. We show that these loci constitute a defining source of the overall ssDNA and Rad52 hotspots in the genome, generating a signature pattern of instability along the chromosomes. We then induce a genome-wide reprogramming of origin usage and evaluate its consequences in our experimental system. This leads to a complete redistribution of the sites of both inappropriate initiation and associated Rad52 recruitment. We therefore conclude that the organization of genome duplication governs the checkpoint control of origin-associated hotspots of instability and plays an integral role in shaping the landscape of genome maintenance.